ATXN2‐AS, a gene antisense to ATXN2, is associated with spinocerebellar ataxia type 2 and amyotrophic lateral sclerosis. Issue 4 (October 2016) - Li, Pan P.; Sun, Xin; Xia, Guangbin; Arbez, Nicolas; Paul, Sharan; Zhu, Shanshan; Peng, H. Benjamin; Ross, Christopher A.; Koeppen, Arnulf H.; Margolis, Russell L.; Pulst, Stefan M.; Ashizawa, Tetsuo; et al.
Abstract : Objective: Spinocerebellar ataxia type 2 (SCA2) is a neurodegenerative disease caused by a CAG repeat expansion in the gene ataxin‐2 ( ATXN2 ). ATXN2 intermediate‐length CAG expansions were identified as a risk factor for amyotrophic lateral sclerosis (ALS). The ATXN2 CAG repeat is translated into polyglutamine, and SCA2 pathogenesis has been thought to derive from ATXN2 protein containing an expanded polyglutamine tract. However, recent evidence of bidirectional transcription at multiple CAG/CTG disease loci has led us to test whether additional mechanisms of pathogenesis may contribute to SCA2. Methods: In this work, using human postmortem tissue, various cell models, and animal models, we provide the first evidence that an antisense transcript at the SCA2 locus contributes to SCA2 pathogenesis. Results: We demonstrate the expression of a transcript, containing the repeat as a CUG tract, derived from a gene ( ATXN2‐AS ) directly antisense to ATXN2. ATXN2‐AS transcripts with normal and expanded CUG repeats are expressed in human postmortem SCA2 brains, human SCA2 fibroblasts, induced SCA2 pluripotent stem cells, SCA2 neural stem cells, and lymphoblastoid lines containing an expanded ATXN2 allele associated with ALS. ATXN2‐AS transcripts with a CUG repeat expansion are toxic in an SCA2 cell model and form RNA foci in SCA2 cerebellar Purkinje cells. Finally, we detected missplicing of amyloid beta precursor protein and N‐methyl‐D‐aspartate receptor 1 in SCA2 brains, consistent with findings in other diseases characterized by RNA‐mediated pathogenesis. Interpretation: These results suggest that ATXN2‐AS has a role in SCA2 and possibly ALS pathogenesis, and may therefore provide a novel therapeutic target for these diseases. Ann Neurol 2016;80:600–615